2018
DOI: 10.15171/joddd.2018.022
|View full text |Cite
|
Sign up to set email alerts
|

Prefabricated resin veneer: A case report of a simplified restorative technique

Abstract: Background: the aim of the study was to describe the step-by-step of clinical cases using prefabricated composite resin veneers (PCRVs), manufactured with the composite Brilliant New Generation (Coltene, Altstätten, Switzerland). Direct composite veneers presented some drawback as the difficult of execution and color instability of the composite over the time. The simplified application of the PCRVs presented as an interesting alternative in cases of smile asymmetry, large deficient restorations and discolored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Regarding the poor esthetic as a consequence of MTA [ 26 , 27 ], indirect composite veneers were revealed to be a suitable solution, considering their properties of surface texture, occlusal stability, tooth integrity, and marginal discoloration resistance [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the poor esthetic as a consequence of MTA [ 26 , 27 ], indirect composite veneers were revealed to be a suitable solution, considering their properties of surface texture, occlusal stability, tooth integrity, and marginal discoloration resistance [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the indirect composite technique also allows a better surface texture, anatomic, occlusal stability, tooth integrity and marginal discoloration to be achieved when compared with a direct restoration, however, studies have shown that there were no statistic differences in the performance of both techniques [26,27]. Thus, in cases of severe enamel discoloration, invasive approaches must sometimes be considered like resin restorations, ceramic veneers, and crowns later on [28].…”
Section: Discussionmentioning
confidence: 99%
“…The developments that have been made in dental materials, especially resin composites and adhesives, have enhanced the clinical performance of resin composite laminate veneer restorations, which allows for the option of minimally-invasive procedures. 1 Laminate veneer restorations are produced using two different techniques: direct and indirect. Depending on the material used, these restorations can be divided into 3 subgroups: acrylic resin, resin composite, and ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although these properties have brought prefabricated resin composite veneers to the forefront of clinical practice, the longest follow-ups reported for these veneers were no longer than 1 year. 1 There have been many studies comparing the clinical performance of laminate veneer restorations in the literature. 3 restorations were evaluated at baseline and thereafter every 6 months for up to 3 years using modified USPHS criteria.\\n\\nRESULTS: Seventeen laminate veneers were bonded onto intact teeth and 29 on teeth having existing resin composite restorations.…”
Section: Introductionmentioning
confidence: 99%